Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres

Mon corps a-t-il un sexe? Sur le genre, dialogues entre biologies et sciences sociales - Gonthier, Josiane; Ruppli-Coursange, Mireille (La Découverte, 2015)
"Sexe" est l'un des mots de la langue française que les gens sans distinction de classe, de religion, d'apparence ou de profession, utilisent avec grand intérêt, qu'ils soient accoudés au zinc d'un bistrot ou à la paillasse d'un laboratoire de biologie moléculaire. Deux mises en scène distinctes, sociale ou scientifique ; deux scénarios différents : d'un côté, les histoires d'amour ou d'imaginaire sexuel, de l'autre, les recherches biologiques. Sous ce mot de "sexe", notre langue, si riche, produit une polysémie bien fâcheuse. L'ambition de ce volume, qui rassemble les contributions de chercheurs et chercheuses en sciences de la vie et en sciences humaines et sociales est de faire le point sur les connaissances concernant le sexe biologique et ses variations, dont on sait désormais qu'il ne permet pas de séparer les individus en deux catégories bien distinctes. Ce livre veut aussi évaluer l'impact du genre sur le développement du corps des êtres sexués et sur la construction de leur identité. Enfin, il cherche à apprécier dans quelle mesure les croyances liées au genre (bicatégorisation mâle-femelle stricte, supériorité masculine) ont pu influencer les recherches menées sur le sexe biologique. Et les témoignages de personnes intersexes et transgenres apportent sur la question de l'identité sexuée un éclairage complémentaire qui bouscule les "réponses" que donnent le plus souvent la médecine et le droit.
Section: 1 vol. (358 p. - [32] p. de pl.) : ill. en noir et en coul. ; 24 cm.
Keywords: approches et analyses; biologie; corps; cours; discipline; discours dominant; premier cycle; psy4910; psychologie; pédagogie; queer; sciences; sciences humaines; sciences sociales; sexualité; systèmes d'oppressions; thématiques; épistémologie; études de genres

Dis/ability studies: theorising disablism and ableism - Goodley, Dan (Routledge, 2014)
In this ground-breaking new work, Dan Goodley makes the case for a novel, distinct, intellectual, and political project – dis/ability studies – an orientation that might encourage us to think again about the phenomena of disability and ability. Drawing on a range of interdisciplinary areas, including sociology, psychology, education, policy and cultural studies, this much needed text takes the most topical and important issues in critical disability theory, and pushes them into new theoretical territory. Goodley argues that we are entering a time of dis/ability studies, when both categories of disability and ability require expanding upon as a response to the global politics of neoliberal capitalism. Divided into two parts, the first section traces the dual processes of ableism and disablism, suggesting that one cannot exist without the other, and makes the case for a research-driven and intersectional analysis of dis/ability. The second section applies this new analytical framework to a range of critical topics, including: The biopolitics of dis/ability and debility Inclusive education Psychopathology Markets, communities and civil society. Dis/ability Studies provides much needed depth, texture and analysis in this emerging discipline. This accessible text will appeal to students and researchers of disability across a range of disciplines, as well as disability activists, policymakers, and practitioners working directly with disabled people.
Section: xvii, 204 pages ; 25 cm
Keywords: EDI; approches et analyses; capacitisme; care; corps; cours; discipline; interdisciplinarité; lit4700; premier cycle; psychologie; pédagogie; santé; sciences de l'éducation; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

Cerveau, sexe et préjugés - Vidal, Catherine (Cerveau, hormones et sexe: Des différences en question, 2012)
"Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d'ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l'information diffusée tient davantage du préjugé, du parti pris idéologique, que d'une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd'hui encore ? C'est de ce constat, et d'un certain sentiment d'exaspération, qu'est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S'appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l'orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d'auteures féministes. Il ne s'agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ?"–Page 4 de la couverture.
Keywords: amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; discipline; discours dominant; fem1000; hétéronormativité; hétérosexisme; neurobiologie; neuropsychologie; pol4102; premier cycle; psy4910; psychologie; québec; régions géographiques; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Brain storm: The flaws in the science of sex differences - Jordan-Young, Rebecca M. (Harvard University Press, 2010)
Jordan-Young has written a stunning book that demolishes most of the science associated with the dominant paradigm of the development of sex and gender identity, behavior, and orientation. The current paradigm, brain organization theory, proposes: "Because of early exposure to different sex hormones, males and females have different brains"; and these hormones also create "gay" and "straight" brains. Jordan-Young interviewed virtually every major researcher in the field and reviewed hundreds of published scientific papers. Her conclusion: "Brain organization theory is little more than an elaboration of longstanding folk tales about antagonistic male and female essences and how they connect to antagonistic male and female natures." She explains, in exquisite detail, the flaws in the underlying science, from experimental designs that make no statistical sense to "conceptually sloppy" definitions of male and female sexuality, contradictory results, and the social construction of normality. Her conclusion that the patterns we see are far more complicated than previously believed and due to a wider range of variables will shake up the research community and alter public perception.
Keywords: LGBTQIA2+; analyse critique; approches et analyses; corps; cours; différence des sexes; discipline; discours dominant; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; revue de la littérature; sciences; sciences humaines; sexe/genre; sexisme; sociologie; systèmes d'oppressions; thématiques

Cerveau, sexe et pouvoir - Vidal, Catherine; Benoit-Browaeys, Dorothée. (Belin, 2005)
À la lumière des connaissances actuelles en neurosciences, on serait tenté de croire que les vieux préjugés sur les différences biologiques entre les hommes et les femmes ont été balayés. Ce n'est manifestement pas le cas : médias et ouvrages de vulgarisation prétendent que les femmes sont " naturellement " bavardes et incapables de lire une carte routière, tandis que les hommes sont nés bons en maths et compétitifs. Ces discours laissent croire que nos aptitudes, nos émotions, nos valeurs sont tablées dans des structures mentales immuables depuis les temps préhistoriques. Cet ouvrage, qui s'adresse à un large public, replace le débat autour de la différence des sexes sur un terrain scientifique rigoureux, au-delà des idées reçues. L'enjeu est de comprendre le rôle de la biologie, mais aussi l'influence de l'environnement social et culturel dans la construction de nos identités d'hommes et de femmes. Notre destin n'est pas inscrit dans notre cerveau! [Source : d'après la 4e de couv.].
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; discours dominant; inégalités; neuropsychologie; neurosciences; premier cycle; psy4910; psychologie; périodes historiques; sciences; sciences humaines; sexe/genre; sexisme; systèmes d'oppressions; thématiques

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Section: x, 193 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis